Women's medical work in early modern France - Broomhall, Susan (Gender in history., 2011)
Situates the practices and perceptions of women's medical work in France in the context of the sixteenth century and its medical evolution and innovations. The book argues that early modern understandings of medical practice and authority were highly flexible and subject to change.